Pendidikan Karakter dalam Kurikulum Nasional Fondasi Integritas untuk Generasi Masa Depan - Cut Kumala Sari; Deby Octa Sitanggang; Siti Sarah Amalia (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
The national curriculum is designed to support the development of students' character education. This is reflected in the integration between subjects and educational levels, as well as attention to the three main domains: attitude (affective), knowledge (cognitive), and skills (psychomotor). The main goal of this curriculum is to shape Indonesian individuals who are faithful, capable of living independently and socially, and who are productive, creative, innovative, and of noble character. The curriculum also encourages students to contribute actively to social life, the nation, and global civilization. Character values are instilled through the development of two main attitudes: spiritual attitude, which refers to practicing one's religious beliefs, and social attitude, which includes honesty, discipline, responsibility, politeness, environmental awareness, and self-confidence in interacting with others.